Effects of cannabidiol on morphine and methylphenidate-induced conditioned place preference during extinction/reinstatement in monkeys and rats - Kashefi, Adel (2020)
Tese (doutorado)—Universidade de Brasília, Programa de Pós-Graduação em Biologia Animal, 2020.